Transformation of Indonesia's Communication System in the Era Of Digitalization - Nur Efitrianisa, Siti (Yayasan Mentari Madani, 2024)
The purpose of this study is to discuss the transformation of communication systems in the digital era. On the other hand, this study also discusses the impact resulting from the transformation of this digital communication system. In the framework of this supporting study, the authors use a qualitative research method. This method is used to describe and analyze the data obtained which is then drawn conclusions in non-numeric form. The results of this study indicate that the transformation of communication systems in the modern world is due to the development of information and telecommunication technology and digital media. More and more areas of contemporary human society and activity are determined by the development of various systems of communication. Twenty-first century communication systems have changed the way we see the world in three important ways: connectivity, authenticity, and style. In this way it is clear that this communication system has changed and caused upheaval in the digital world which can be achieved easily